OOSM : stay home or go abroad? - Steiger, Marvin, (SAGE Knowledge. Cases., 2017)
Bruner had a revolutionary idea about a new solution for digital screen signage while working for a digital marketing company in Slovenia. When the company he was working for went bankrupt, he decided to found OOSM, a B2B digital signage start-up, with two friends. A few months later, they decided to enter the Western European market because the Slovenian market was rather small and short of investors interested in high tech start-ups. However, at that time, Bruner had a founding team from Slovenia, a technical team from Pakistan, and his product was made in China. This combination did not look favorable, not only to OOSM's potential clients but also to potential investors. Bruner knew he had a good idea, a motivated team and a quality product, but he also knew he needed credibility and validation to be able to enter the Western European market. What approach should he take in such a situation?